EVALUATION OF BODY COMPOSITION, QUALITY OF LIFE AND PHYSICAL FITNESS IN CLIMACTERIC WOMEN. (Fiep Bulletin - online, 2016)
The transition period between reproductive life and climacteric brings significant alterations in the life of a woman. The objective of this study is to evaluate the body composition, quality of life and physical fitness of post-menopausal women. The body composition was measured by the bioelectric impedance, the quality of life by two questionnaires (Cervantes Scale and Women General Health Questionnaire) and for the physical fitness Ebbling treadmill test. The results were determined by average and standard deviation for: BMI 29±4, WC 86±8, %F 38±5, %MM 62±5, VO2max 31,5±5,5 mlO2.kg-1.min-1. 80% with vasomotor symptomology, 70% cognitive impairment, 63% with sleeping disorder and 56% with anxiety and attractiveness or self-esteem symptoms. In the CS there was greater symptomology in the menopause and health domain that evaluate vasomotor symptoms, health and aging, all of them compromising the quality of life. Evaluated women presented physical fitness below average in the treadmill test. In this context, the characterization of climacteric women's health suggests future studies of intervention to optimize the inadequate indicators.
Keywords: post-menopausal women; body composition; quality of life.